2013
DOI: 10.2136/sssaj2012.0304
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water and Salinity Distribution under Different Treatments of Drip Irrigation

Abstract: In this study, field experiments and numerical simulations for different drip irrigation treatments in a sandy loam soil were conducted to investigate soil water and salinity distribution as well as dye infiltration patterns. Three treatments, surface drip irrigation without and with plastic mulch (T1 and T2, respectively) and subsurface drip irrigation (T3), were used. Daily and bi‐weekly irrigation regimes were used for each treatment. After completion of each irrigation treatment, horizontal soil sections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Consequently, the influences of the same irrigation water salinity with different irrigation water amounts on soil salinity values are closely related to the irrigation water salinity. This conclusion is confirmed with those reported by Chen and Feng (2013), Assouline et al, (2006) and Selim et al, (2013) Under drip irrigation system, the soil salinity average values of active root zone at the end of harvesting growth stage of tomatoes subjected to deficit irrigation of 100, 75 and 50 % ETc using highly saline water (9.15dSm -1 ) were the lowest values (Table 2). Consequently, this stage is the lowest stage as affected by deficit irrigation depths of 75 and 50% ETc using highly saline water of 9.15dSm -1 than that obtained for other growth stages, the soil salinity average values of active root zone at the end of flowering growth stage were high.…”
Section: Soil Salinity Under Drip and Gated Pipe Irrigation Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, the influences of the same irrigation water salinity with different irrigation water amounts on soil salinity values are closely related to the irrigation water salinity. This conclusion is confirmed with those reported by Chen and Feng (2013), Assouline et al, (2006) and Selim et al, (2013) Under drip irrigation system, the soil salinity average values of active root zone at the end of harvesting growth stage of tomatoes subjected to deficit irrigation of 100, 75 and 50 % ETc using highly saline water (9.15dSm -1 ) were the lowest values (Table 2). Consequently, this stage is the lowest stage as affected by deficit irrigation depths of 75 and 50% ETc using highly saline water of 9.15dSm -1 than that obtained for other growth stages, the soil salinity average values of active root zone at the end of flowering growth stage were high.…”
Section: Soil Salinity Under Drip and Gated Pipe Irrigation Methodssupporting
confidence: 90%
“…Chen and Feng, (2013) in their study on the dynamics of soil water-salt transportation and its spatial distribution characteristics under irrigation with saline water in a maize field experiment under furrow irrigation system revealed that the irrigation with water of high salinity could effectively increase soil water content, but the increment is limited comparing with the influence from irrigation amount. Under drip irrigation system, Selim, et al, (2013) concluded that the daily irrigation regime kept the top soil layer moist with adequate amount of soil water as compared to the bi-weekly irrigation. On the other hand, Badr and Abou Hussein (2008) concluded that the soil water content under 1.4 ETc was much higher than under 1.0 ETc and 1.2 ETc for all soil depths.…”
Section: Introductionmentioning
confidence: 99%
“…However, constraint conditions for determining optimal irrigation strategy would be more complicate if we focus on the whole crop growth period for some other factors such as root water uptake and water and salt stress should be taken into consideration [39,40]. Although in conditions of before sowing like our study, factors such as field slope, farming practices (eg tillage, no tillage, and plastic mulched) will also affect the soil water, salt, and NO 3 --N distributions after irrigation [41] and these might be 2D/3D issues and will be studied in our future work.…”
Section: Irrigation Strategies Determinationmentioning
confidence: 95%
“…Burt and Isbell [25] found that mulched drip irrigation was able to maintain moderate soil matric potential, help control weeds and promote crop production. Selim et al [26] also indicated that the problem associated with salinity could be overcome effectively under mulched drip irrigation because of controlled leaching and that plastic film mulch has significant effects on soil water, soil thermal and salinity distribution.…”
Section: Introductionmentioning
confidence: 99%